Performance Analysis of Multiple Input Multiple Output (MIMO) Multi-Carrier Code-Division Multiple Access (MC-CDMA) Combined with Quasi-Orthogonal Space Time Block Coding (QO-STBC) in Rayleigh Fading Channel - Kusumawardhani, Eka; Astuti, Rina Pudji; Adriansyah, Nachwan Mufti; Imansyah, Fitri; Putra, Leonardus Sandy Ade (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2022)
The need for a communication system with a higher data rate and mobility grows along with information and communication technology development. Combining MC-CDMA with the MIMO system and supporting the system with a good transmit diversity technique is a promising idea to provide the needed communication system, especially in high mobility conditions. MC-CDMA can support ubiquitous communications without affecting the achievable BER and is more capable of high-speed mobility. It integrates the benefit of both OFDM and CDMA. On the other hand, QO-STBC increases the bit rate without using additional bandwidth to transmit diversity in the MIMO system. So, this study proposed a system combining the MIMO MC-CDMA system with QO-STBC. The proposed system is investigated under high mobility conditions to see the system's performance. The simulation results show that our system performs better than the MC-CDMA STBC system and the QOSTBC system but not better than the MC-CDMA multilevel coding scheme. To reach the value of BER 10−3, MC-CDMA multilevel Coding requires less power, around 5 dB, than the proposed system.